Hydrogen generation from sodium borohydride via natural materials - Levent Semiz (International Journal of Pioneering Technology and Engineering)
In this study, the catalytic activity of starch, cellulose and coffee were investigated in the dehydrogenation of sodium borohydride. The hydrogen generation rates of starch, cellulose and coffee were measured as 4.0, 6.7 and 60 ml H2 min-1 g-1 and the activation energies of the reactions were calculated as 27.4, 17.1 and 14.5 kJ mol-1 for  starch, cellulose and coffee respectively. The study showed that natural sources could be used directly as catalysts in the dehydrogenation of chemical hdyrides.